Rozwiąż równania:

b) 4 - 2 (5 - x) = x - 4 (x - 1)
c) 7 - (3x + 4) = (x + 1) - (2x + 4)
d) x + 3 - (4 - x) = 3x - (2x - 3)

Błagam pomóżcie!! Dam najjj :***

Aha i wiem że w b) ma wyjść wynik 2
w c) ma wyjść wynik 3
a w d) ma być 4

Dzieki :)

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-19T17:40:43+01:00
B) 4 - 2 (5 - x) = x - 4 (x - 1)
4-10+2x=x-4x+4
-6+2x=-3x+4
5x=10/:5
x=2

c) 7 - (3x + 4) = (x + 1) - (2x + 4)
7-3x-4=x+1-2x-4
3-3x=-x-3
-2x=-6/:-2
x=3

d) x + 3 - (4 - x) = 3x - (2x - 3)
x+3 -4 +x =3x-2x+3
2x-1=x+3
x=4
2 5 2
2010-01-19T17:41:35+01:00
B)
4 - 2 (5 - x) = x - 4 (x - 1)
4-10+2x=x-4x+4
2x-x+4x=4-4+10
5x=10
x=2

c)
7 - (3x + 4) = (x + 1) - (2x + 4)
7-3x-4=x+1-2x-4
-3x+2x-x=-4+1-7+4
-2x=-6
x=3

d)
x + 3 - (4 - x) = 3x - (2x - 3)
x+3-4+x=3x-2x+3
x+x-3x+2x=3-3+4
x=4
2010-01-19T17:42:49+01:00
B)4 - 2 (5 - x) = x - 4 (x - 1)
4-10+2x=x-4x+4
2x-6=-3x+4
5x=10
x=2
c)7 - (3x + 4) = (x + 1) - (2x + 4)
7-3x-4=x+1-2x-4
3-3x=-x-3
2x=6
x=3
d)x + 3 - (4 - x) = 3x - (2x - 3)
x+3-4+x=3x-2x+3
2x-1=x+3
x=4